FAKTOR–FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN KLIEN DENGAN HEMOPTISIS DI RSD KALISAT KABUPATEN JEMBER - Firdha Novitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2014)
Tuberculosis (Hemoptysis) is the most common disease found in society today. Repeated hemoptysis should be suspected as a serious illness, so this causes anxiety for the client. The purpose of this study was to study the factors associated with anxiety in clients with hemoptysis in the Kalisat Kalisat International space at Jember Regency. This research design This study uses a